Law Enforcement Issues in Natural Resource Legislation - VIVCHARENKO, Oleh A.; MOROZ, Galyna V.; KOKHAN, Nataliya V. (Journal of Environmental Management and Tourism, 2020)
Natural resource legislation is determined by the fact that for its full functioning it is necessary to create an integrated system of legal measures. The relevance of the work is determined by the fact that the use of the environment is currently being considered in an industry context and there is no synergistic assessment of the balance between the legal assessment of environmental impact and the structural content of the natural resource legislation industry. The novelty of the study is determined by the fact that for the first time in the article the current complex of natural resource legislation is considered, which studies the environment not as a complex of differentiated industries, but as a single environment in which the interaction between man and nature takes place. The authors of the article determine the possibility and necessity of a unified regulation of environmental management and the formation of an integrated national system of not only natural resource, but also environmental legislation. The practical application of the study is possible in the development of economic methods and measures for environmental protection, which will take into account the possibilities of environmental compensation